Chloroplast genomes as a tool to resolve red algal phylogenies: a case study in the Nemaliales - Costa, Joana F. (2016)
Obtaining strongly supported phylogenies that permit confident taxonomic and evolutionary interpretations has been a challenge in algal biology. High-throughput sequencing has improved the capacity to generate data and yields more informative datasets. We sequenced and analysed the chloroplast genomes of 22 species of the order Nemaliales as a case study in the use of phylogenomics as an approach to achieve well-supported phylogenies of red algae.